(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2016)
The Act 40/2015 that establishes the Legal Regime of the Public Sector, brings as one of its major innovations the regulation of state institutional public sector as inclusive concept of entities of various kinds that have been including in the doctrinal concept of Institutional Administration which until now were regulated in a dispersed manner. In the present study we will thresh the main changes in this area, both in general and for each type of bodies integrated into the new concept that has been mentioned, and whose main objective is to increase rationality, effectiveness and efficiency of the Institutional Administration, as one of the fundamental elements of the Spanish Public Administration.